Anomalous origin of right pulmonary artery from innominate artery: Repair using pulmonary artery pedicled flap plasty - Roy Varghese; Jai Ganesh; Jeeva Nandam; Sujathaa Ravikumar; Sivakumar Kothandam (Annals of Pediatric Cardiology, 2017)
Origin of the right pulmonary artery from innominate artery is an exceedingly rare anomaly. We report two cases with this anomaly that underwent surgical repair. The surgical technique described achieves tissue-to-tissue anastomosis using a pedicled flap from the main pulmonary artery.